2013
DOI: 10.4103/1755-6783.116506
|View full text |Cite
|
Sign up to set email alerts
|

Situation of P. vivax malaria in Ahmedabad city: A study in purview of national guidelines

Abstract: Introduction: Malaria is still the most important cause of morbidity-mortality in India. National vector borne disease control program (NVBDCP) in urban areas is implemented through UHCs. In Gujarat, 89,764 malaria cases were reported in 2011 with 127 deaths, with 17.9% of them being the vivax cases. Ahmedabad is at the receiving end of malaria menace due to its rapid growth. Compared to 2011, significant rise in number of Plasmodium vivax (Pv) cases has been observed in Ahmedabad in 2012. Aims and Objectives:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…In addition, there was a significantly positive correlation between OD values and parasitemia levels (r: 0.980, p : 0.000 for blood, r: 0.990, p : 0.000 for serum) in the present study ( Figure 4 ). Similar findings were reported by Joshi et al. (2004) in Plasmodium vivax infections of humans, and by Luo et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, there was a significantly positive correlation between OD values and parasitemia levels (r: 0.980, p : 0.000 for blood, r: 0.990, p : 0.000 for serum) in the present study ( Figure 4 ). Similar findings were reported by Joshi et al. (2004) in Plasmodium vivax infections of humans, and by Luo et al.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, there was a significantly positive correlation between OD values and parasitemia levels (r: 0.980, p: 0.000 for blood, r: 0.990, p: 0.000 for serum) in the present study (Figure 4). Similar findings were reported by Joshi et al (2004) in Plasmodium vivax infections of humans, and by Luo et al (2012) in B. microti infections of hamsters. Luo et al (2012) revealed that circulating Babesia microti-secreted antigen 1 (BmSA1) overlaps with the parasitemia profile during active infections in a hamster model.…”
Section: Tick Attachmentsupporting
confidence: 89%
“…A complex health system of public and private providers adds to the socioeconomic and environmental factors to increase the complexities of malaria control and elimination in India 24 . In India, the National Vector Borne Disease Control Programme is a vertically implemented nationwide programme 25 . Health is the responsibility of the state; therefore, malaria controlis primarily carried out by the states under the overall guidance of the programme 26 The true burden of malaria in India isunder-reported as a result of poor surveillance, inadequate collaboration between the private health sector and the government, and the inability to make accurate estimates of populations at risk 27 .…”
Section: Challenges Of Malaria Eliminationmentioning
confidence: 99%
“…Gujarat is one of the major states contributing to the Pv burden in India, with a Pv / Pf ratio around 80:20 [ 12 ]. Remarkably, about one in five malaria-associated deaths reported in that state has been attributed to Pv [ 12 , 13 ]. This is in line with the mounting evidence for the ability of Pv to induce a wide spectrum of severe malaria, with a risk of death similar to that observed for Pf infection [ 3 , 7 , 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%